A hemicryptophane with a triple-stranded helical structure - Augustin Long; Olivier Perraud; Erwann Jeanneau; Christophe Aronica; Jean-Pierre Dutasta; Alexandre Martinez (Beilstein Journal of Organic Chemistry, 2018)
A hemicryptophane cage bearing amine and amide functions in its three linkers was synthesized in five steps. The X-ray molecular structure of the cage shows a triple-stranded helical arrangement of the linkers stabilized by intramolecular hydrogen bonds between amide and amine groups. The chirality of the cyclotriveratrylene unit controls the propeller arrangement of the three aromatic rings in the opposite part of the cage. 1H NMR studies suggest that this structure is retained in solution.